High-frequency repetitive transcranial magnetic stimulation at dorsolateral prefrontal cortex for migraine prevention: A systematic review and meta-analysis - Nabil Izzaatie, Mohamad Safiai; Nur Afiqah, Mohamad; Hamidon, Basri; Liyana Najwa, Inche Mat; Hoo, Fan Kee; Anna Misyail, Abdul Rashid; Abdul Hanif Khan, Yusof Khan; Loh, Wei Chao; Janudin, Baharin; Fernandez, Aaron; Intan Nureslyna, Samsudi; Mohd Hazmi, Mohamed; et al. (SAGE Publications, 2022)
Objective: To evaluate the efficacy of high-frequency repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex as a migraine prevention by conducting a systematic review and meta-analysis.